Malaya media warfare in World War-II during the Japanese invasion (1941-1945): propaganda airborne leaflets / Wardatul Hayat Adnan and Dazmin Daud - Adnan, Wardatul Hayat; Daud, Dazmin (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2020)
In the history of World War II, Japanese invasion in Malaya (1941-1945) was not a forgotten war but the apogee of a propaganda war. By analysing the contents of propaganda leaflets distributed during the Japanese invasion is important in understanding the communication used in defeating, surviving in a war-incorrect grammar and sentence structure). The present study aims to explore the airdropped (propaganda) leaflets using the 10 steps of analysing propaganda and to identify types of leaflets used in communicating to its target audience. Findings showed that the frames of 'demoralization', encouraging surrender, survival and building trust were most frequently used during the overall war period in Malaya. These leaflets were frequently dropped towards the end of the war with its target in overriding and controlling Malayan people. The leaflets were varied and depended on the target audiences, for instance, different language was used for different target audience and for different propaganda objectives.